IgG4-related disease with massive pericardial effusion diagnosed clinically using FDG-PETCT: a case report - Wei, Qiaofeng; Qi, Huili; Wei, Hongmei; Wang, Xiuhua; Zhang, Hongju (Frontiers in Immunology, 2023)
Background IgG4-related disease (IgG4-RD) is a systemic inflammatory disease which involves various organs such as the pancreas, lacrimal gland, salivary gland, retroperitoneum, and so on. These organs can be affected concomitantly. 18-Fluorodeoxyglucose positron emission tomography computed tomography (FDG-PETCT) is a systemic examination which can identify active inflammation and detect multiple organ involvement simultaneously. Pericardial involvement is rare in IgG4-RD, early detection and treatment can greatly improve the prognosis of patients. Case summary We reported a 82-year-old female patient referred to our department complaining of chest tightness and abdominal fullness for 8 months and massive pericardial effusion for 2 months. A large amount of pericardial effusion was found during the hospitalization of Gastroenterology. Then she was transferred to cardiology. Although infectious, tuberculous, and neoplastic pericardial effusions were excluded, there was still no diagnosis. The patients were examined by FDG-PETCT which considered IgG4-RD. After coming to our department, the results of the patient’s laboratory tests showed that immunoglobulin subgroup IgG4 was 14.0 g/L. Then we performed a biopsy of the right submandibular gland. Pathological morphology and immunohistochemistry suggested IgG4-RD. Combined with level of IgG4, clinical, pathological and immunohistochemical results, we determined the final diagnosis of IgG4 related diseases. Then we gave glucocorticoid and immunosuppressant treatment. At the end, pericardial effusion was completely absorbed. As prednisone acetate was gradually reduced, no recurrence of the disease has been observed. Conclusion Pericardial effusion can be the initial presentation in IgG4-RD. For patients with massive pericardial effusion of unknown cause, early detection of IgG4 is recommended, and PETCT may be helpful for obtaining the diagnosis.